2007
DOI: 10.1080/10942910601048994
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical and Functional Properties of Sour Starches from Different Cassava Varieties

Abstract: This article reports our investigation on the effect of cassava varieties on the physicochemical and functional properties of sour starches. There were significant differences (P < 0.05) in the ash, pH, amylose, amylopectin, starch damage, total titratable acidity (TTA), sugar, and starch content but not moisture contents of various cassava sour starches. There were no significant differences (P > 0.05) in Water Absorption Capacity (WAC), swelling power, and solubility index, while significant differences were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
77
4
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(102 citation statements)
references
References 23 publications
17
77
4
4
Order By: Relevance
“…Consequently, the lower SWP obtained in TMS01/1371 BfCRS might suggest a more highly ordered arrangement in its granules than that of TMS01/1368 with the highest SWP. Nevertheless, the SWP obtained in this work for TMS01/ 1368 BfCRS was within the range reported by Onitilo et al [20] and Eke et al [21] but lower to that of Kay [22] for dried white-fleshed cassava root starches (WfCRS). This could be due to varietal differences.…”
Section: Discussionsupporting
confidence: 68%
“…Consequently, the lower SWP obtained in TMS01/1371 BfCRS might suggest a more highly ordered arrangement in its granules than that of TMS01/1368 with the highest SWP. Nevertheless, the SWP obtained in this work for TMS01/ 1368 BfCRS was within the range reported by Onitilo et al [20] and Eke et al [21] but lower to that of Kay [22] for dried white-fleshed cassava root starches (WfCRS). This could be due to varietal differences.…”
Section: Discussionsupporting
confidence: 68%
“…There is a significant different (p<0.05) in both white and yellow Ogi. Onitilo (2007) have suggested that the swelling power granules reflect the extent of the association forces within the granules. Swelling power and solubility of the starches provide evidence of non covalent bonding between molecules within the starch granules.…”
Section: Resultsmentioning
confidence: 99%
“…The extensive thermal breakdown of the starch in the parboiled sample may have caused the very low viscosity values. Pasting profile of flour has been found to be influenced by its starch [19], protein [20], lipid [21] contents and the degree of starch damage during processing [22,23].…”
Section: Pasting Propertiesmentioning
confidence: 99%